MoneyZen : the secret to finding your "enough" - Thakor, Manisha; Sweetingham, Lisa (Harper Business, 2023)
"Thakor shares stories from her experiences and lessons she's learned, offering a touchstone for what she calls true "wealth"-the convergence of financial and emotional health"--Provided by publisher.